2020
DOI: 10.1016/j.omto.2020.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Virus-Mediated Targeting of the ERK Signaling Pathway Inhibits Invasive Propensity in Human Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) cells have an exceptional ability to invade nerves through pronounced crosstalk between nerves and cancer cells; however, the mechanism of PDAC cell invasion remains to be elucidated. Here, we demonstrate the therapeutic potential of telomerase-specific oncolytic adenoviruses, OBP-301 and tumor suppressor p53-armed OBP-702, against human PDAC cells. Highly invasive PDAC cells exhibited higher levels of phosphorylated extracellular signal-regulated kinases 1 and 2 (ERK1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Iodine‐125 seeds planted in the local sites of tumors even relieved pain in PDAC patients [ 124 ]. It has also been reported that telomerase‐specific oncolytic adenoviruses might have therapeutic potential for PDAC patients [ 125 ]. Moreover, these viruses repressed the migration and invasion of pancreatic cell lines in a DRG co‐culture system [ 125 ], indicating their potential role in preventing PNI.…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine‐125 seeds planted in the local sites of tumors even relieved pain in PDAC patients [ 124 ]. It has also been reported that telomerase‐specific oncolytic adenoviruses might have therapeutic potential for PDAC patients [ 125 ]. Moreover, these viruses repressed the migration and invasion of pancreatic cell lines in a DRG co‐culture system [ 125 ], indicating their potential role in preventing PNI.…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
“…It has also been reported that telomerase‐specific oncolytic adenoviruses might have therapeutic potential for PDAC patients [ 125 ]. Moreover, these viruses repressed the migration and invasion of pancreatic cell lines in a DRG co‐culture system [ 125 ], indicating their potential role in preventing PNI. Overall, comprehensive multidisciplinary clinical trials are urgently needed to optimize the treatment of PDAC patients.…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
“…In addition, the OBP-702 can activate p53, while OBP-301 does not activate p53 in PC. Therefore, OBP-702, p53-armed oncolytic virotherapy, could be a promising strategy for PC [ 51 ]. Mechanically, OBP-702 effectively inhibited the invasion of PC cells by inhibiting ERK signaling.…”
Section: Modified Ovsmentioning
confidence: 99%
“…To overcome these unfavorable TMEs in pancreatic cancer, several OVs have been investigated in preclinical in vivo models, and some OVs are already under development in phase I and II clinical trials. An oncolytic adenovirus, OBP-702, expressing tumor suppressor p53, significantly suppressed tumor growth in an orthotropic xenograft model of pancreatic cancer by disruption of extracellular signal regulated kinase (ERK) signaling [ 60 ]. Oncolytic adenovirus (ONYX-015, VCN-01, LOAd703), oncolytic HSV (T-VEC, HF10, Orien X010), and pelareorep (Reolysin) are now in phase I or phase II clinical trials [ 33 ].…”
Section: Ov Monotherapymentioning
confidence: 99%